Clinical Diagnostics in Patients with Cerebral Infarction Due To Covid-19 - Jumraini Tammasse; Muhammad Iqbal Basri; Muhammad Akbar (Indian Journal of Forensic Medicine & Toxicology, 2021)
The Corona Virus Disease 19 (COVID-19) outbreak is a deadly disease of concern to the world, includingIndonesia. Reported cases of death show a high number with more than 3800 deaths reported. This diseasecan induce Cytokine Storm Syndrome (CSS) and interfere with the Blood-Brain Barrier (BBB), causingcoagulopathy and hypoxia, which in turn lead to cerebral edema in the brain. This research uses a casestudy approach, with a detailed examination of one event. In this case, cerebral infarction was caused byCOVID-19 as evidenced by laboratory results in the presence of symptoms of inflammation, CSF, sepsis,and coagulopathy. These symptoms can result in cerebral infarction and hypercoagulability. therapeuticinterventions are carried out in reducing inflammation, reducing cerebral edema, and preventing secondaryinfection. COVID-19 in this case can have a deleterious effect on patients with cerebral infarction. Propertreatment is needed to give better results.